Performance Implications of Environment-Strategy-Governance Misfit - Gani, Lindawati; Jermias, Johnny (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
This study examines the impacts of matching competitive environment, business strategy, and corporate governance structure on firm performance. We predict that in a dynamic environment, firms pursuing a product differentiation strategy will perform better than firms pursuing a strategy of cost leadership, but the performance differential is affected by the level of board independence and managerial share ownership. In a stable environment, we predict that firms pursuing a strategy of cost leadership will perform better than firms pursuing a product differentiation strategy, and the performance differential is affected by the level of board independence and managerial share ownership. Overall, the results are consistent with the predictions of this study. Board independence and managerial ownership affect the performance differential between product differentiators and cost leaders in a dynamic environment. In a stable environment, however, the results are not statistically significant.